For some mothers more than others: How children matter for labour market outcomes when both fertility and female employment are low - Krzysztof Karbownik; Michal Myck (Uppsala University, Department of Economics, 2012)
We estimate the causal relationship between family size and labour market outcomes for families in low fertility and low female employment regime. Family size is instrumented using twinning and gender composition of the first two children. Among families with at least one child we identify the average causal effect of an additional child on mother's employment to be -7.1 percentage points. However, we find no effect of additional children on female employment among families with two or more kids. Heterogeneity analysis suggests no causal effects of fertility on female employment among mothers with less than college education and older mothers (born before 1978). Furthermore, we find evidence for the interaction of family size with maternal education and age. An unintuitive feature of our finding is that we identify a positive bias of OLS estimates for highly educated mothers and for mothers born after 1977.
urn:nbn:se:uu:diva-182873
Keywords: J13; J22; 330; labour supply; family size; female employment; Familiensoziologie; Weibliche Arbeitskräfte; Erwerbstätigkeit; Fertilität; Schätzung; Polen